(untitled) (Research, Society and Development, 2021)
The present study aimed the characterization of the clinical-epidemiological profile of people living with HIV(PVHIV) living in the state of Pará. We included all people, independent of age or sex, whose samples was sent to the Central laboratory of Pará (LACEN-PA) during 2013 to 2015 for the genotyping HIV testing. The data were obtained through the collection of information in the results reports stored in LACEN-PA. Information were collected as sex, age, level of education, race, year of diagnosis, raison related to the change in therapeutic regimen and presence of mutations. The male gender was predominant, aged between 40 and 50 years or more, brown and with elementary education. Most were diagnosed with HIV between the years 2000 and 2009, with the majority showing changes in the therapeutic regimen. This fact was largely due to the presence of therapeutic failure and intolerance, thus corroborating the presence of mutations. In this present study, we observed an epidemiological profile of PLHIV consistent with the literature, characterized by the prevalence of the male gender, with the age group between 40 and 50 years or more, mixed race and education at the fundamental level. It was also possible to observe a high rate of changes in therapeutic regimens, of therapeutic failure, in addition to high rates of mutations for the pharmacological classes used in antiretroviral therapy. Thus, demonstrating the importance of genotyping exams not only for choosing the most appropriate therapy but also for adopting strategies that seek to improve PLHIV adherence to treatment with antiretrovirals. Further, new studies contributing to understand and to identificate the changes in therapeutic regimens, as well as their contribution to the appearance of mutations and consequent therapeutic failure, are needed.